Circadian Clock and Photoperiodic Flowering in Arabidopsis: CONSTANS Is a Hub for Signal Integration. Issue 1 (29th September 2016) - Shim, Jae Sung; Kubota, Akane; Imaizumi, Takato
Abstract : The circadian clock and light signaling regulate CONSTANS function through intricate mechanisms that reside in phloem companion cells of leaves for controlling photoperiodic flowering in Arabidopsis.